A deafening inequality. Portuguese deaf education and the call for debationg audism in schools - Schwachten, Lejo (2011)
The emancipation of the deaf community represents a vivid history in which the right to use sign language and deaf culture had to be defended over and over again, against oralists, scientists, politicians, industries and pedagogues. It is a history of hearing oppression, of different views about what makes one human. In this article, the authors give a historical account from an audist perspective and question if it is not urgent to promote another pedagogical approach in the education of deaf and hearing, which include debating personal and structural audism in schools.